한국에서의 담뱃갑 경고그림 도입과정 분석연구: 국회 보건복지위 회의록 분석을 중심으로 - 황지은; Ji-eun Hwang; 조성일; Sung-il Cho (Health policy and management, 2016)
Graphic health warning on the tobacco product package is a cost-effective tobacco control policy to convey information on harmful effect of tobacco use to health, and it is known not only to motivate smokers to quit but also to deter adolescents from start smoking. In case of Korea, amendments to National Health Promotion Act requiring implementation of graphic health warning had been submitted 13 times, from 2002 to May 2015. In May 2015, the amendment had been approved by the National Assembly and it enters into force on December 23, 2016. This research analyzed the discussions from Health and Welfare Committee of the National Assembly during the implementation of the graphic health warning in order to study decision making process of legislators. Study found that there was a shift from a general opposition on implementing graphic health warning at first to a harsh conflict over relaxation of the regulation once discussing the implementation in earnest. Particularly, while the group supporting the implementation of the graphic health warning or opposing relaxation advocated the amendment with scientific and knowledge-based evidences including the World Health Organization Framework Convention on Tobacco Control, the group opposing the adoption of the amendment itself or suggesting relaxation tended to defend their position with empathy on smokers or tobacco industries.